Bitemporal Complex Event Processing of Web Event Advertisements. - Furche, T; Grasso, G; Huemer, M; Schallhart, C; Schrefl, M (Springer, 2013)
The web is the largest bulletin board of the world. Events of all types, from flight arrivals to business meetings, are announced on this board. Tracking and reacting to such event announcements, however, is a tedious manual task, only slightly alleviated by email or similar notifications. Announcements are published with human readers in mind, and updates or delayed announcements are frequent. These characteristics have hampered attempts at automatic tracking. PeaCE provides the first integrated framework for event processing on top of web event ads. Given a schema of events to be tracked, the framework populates this schema through compact wrappers for event announcement sources. These wrappers produce events including updates and retractions. PeaCE then queries these events to detect complex events, often combining announcements from multiple sources. To deal with updates and delayed announcements, PeaCE's schemas are bitemporal so as to distinguish between occurrence and detection time. This allows complex event specifications to track updates and to react to differences in occurrence and detection time. Our evaluation shows that extracting the event from an announcement dominates the processing of PeaCE and that the complex event processor deals with several event announcement sources even with moderate resources. We further show, that simple restrictions on the complex event specifications suffice to guarantee that PEACE only requires a constant buffer to process arbitrarily many event announcements. © 2013 Springer-Verlag.